Cr(VI) removal performance from wastewater by microflora isolated from tannery effluents in a semi-arid environment: a SEM, EDX, FTIR and zeta potential study - Aké, Aké Henri Joël; Rochdi, Nabil; Jemo, Martin; Hafidi, Mohamed; Ouhdouch, Yedir; El Fels, Loubna (Frontiers in Microbiology, 2024)
Hexavalent chromium removal from the environment remains a crucial worldwide challenge.To address this issue, microbiological approaches are amongst the straightforward strategies that rely mainly on the bacteria's and fungi's survival mechanisms upon exposure to toxic metals, such as reduction, efflux system, uptake, and biosorption. In this work, scanning electron microscopy, energy-dispersive X-ray spectrophotometry, Fourier transform infrared spectroscopy, and zeta potential measurements were used to investigate the ability of chromium adsorption by Bacillus licheniformis, Bacillus megaterium, Byssochlamys sp., and Candida maltosa strains isolated from tannery wastewater. Scanning electron microscopy combined with energy dispersive X-ray spectroscopy revealed alterations in the cells treated with hexavalent chromium. When exposed to 50 mg/L Cr 6+ , Bacillus licheniformis and Candida maltosa cells become rough, extracellular secretions are reduced in Bacillus megaterium, and Byssochlamys sp. cells are tightly bound and exhibit the greatest Cr weight percentage. In-depth analysis of Fourier transform infrared spectra of control and Cr-treated cells unveiled Cr-microbial interactions involving proteins, lipids, amino acids, and carbohydrates. These findings were supported by zeta potential measurements highlighting significant variations in charge after treatment with Cr(VI) with an adsorption limit of 100 mg/L Cr 6+ for all the strains. Byssochlamys sp. showed the best performance in Cr adsorption, making it the most promising candidate for treating Cr-laden wastewater.